Complexity in the spatial utilization of rangelands: Pastoral mobility in the Horn of Africa. (September 2017) - Liao, Chuan; Clark, Patrick E.; DeGloria, Stephen D.; Barrett, Christopher B.
Abstract: Extensive movement is a key strategy for pastoralists to ensure adequate forage intake for livestock while distributing grazing pressure throughout the landscape. However, the complexity of pastoral mobility was overgeneralized in previous research, which often leads to sedentarization-oriented policy-making. Based on continuous GPS-tracking of cattle movement over seven months and pastoralist knowledge of mobility, we investigated spatial rangeland utilization patterns in five study sites across the Borana Zone of southern Ethiopia. By quantifying the extent of movement, density of utilization, and recursive use of rangelands, we found highly diverse mobility patterns and resource-use strategies even within a single study region. Rather than the central-place model, pastoral mobility patterns in Borana can be characterized using restrictive, semi-extensive, or extensive herding models. The research findings suggest that sedentarization largely results in compromised mobility. Thus, we recommend both intra- and inter-community coordination to reduce recursive use of rangelands and mitigate degradation. Highlights: We conducted continuous GPS-tracking of cattle movement in Ethiopia. We found highly diverse pastoral mobility patterns and resource-use strategies. Sedentarization results in compromised mobility and recursive use of rangelands. We recommend coordinated grazing to mitigate rangeland degradation.